Secondary Seizures in the Pediatric Population in Two Tertiary Hospitals in India - Arun Kumar; Thangaraj Marimuthu; Lakshminarayanan Kannan; Vikash Agarwal; Dinesh Nayak (International Journal of Integrated Health Sciences, 2023)
Objective: To evaluate the clinical pattern of secondary seizures which includes acute and remote symptomatic seizures among hospitalized patients in two healthcare centers and to assess the outcomes among hospitalized patients having secondary seizures.